Design And Analysis Performance of Liquid Petroleum Gases System in Residential Building; Review (Journal of Engineering, 2022)
Liquefied petroleum gases (LPG) consist of hydrocarbons obtained by refining crude oil, either from propane or butane or a mixture of the two. There are often other components such as propylene, butylene or other hydrocarbons, but they are not the main component. The study aims to review previous studies dealing with designing an LPG system to deliver gas to residential campuses and buildings. LPG is extracted from natural gas NG by several processes, passing through fractionation towers and then pressuring into CNG storage tanks. Gas contains several problems, including gas leakage through the pipes and leads to fires or explosions in LPG storage and distribution tanks, so safety conditions were taken in the design and implementation. The major results are the gas leak detector showed that rapid response to gas leakage sense, so it is recommended to place the device at a distance of 0.6-2 meters from the gas source and at a distance of 0.2 to 1 meter above the ground, and the major conclusion is new techniques for using hardware and software components must be demonstrated again that can be applied to models to show fast and effective results.